Marseille, port to port - Kornblum, William (Columbia University Press, 2022)
"Marseille is for city lovers, especially those with a sense of adventure and some historical imagination. In Marseille you'll discover an ancient and joyful French seaport, bathed in Mediterranean sunshine and shaded in the ochre hues of Provence. It is France's second city in population, largest in territory, and its "mauvais sujet". It is a city that puts the social and political fault lines of contemporary French society on display for those willing to look. For all of its lived in charm, Marseille can't shake its reputation for crime and corruption, but if you get beyond this, as William Kornblum does in Marseille, Port to Port, the historic streets of the city tell the stories of fires, plagues, wars, obsolescence, and regeneration. Generations have fought through ethnic and racial differences. Marseille suffered occupation and destruction during World War II, and much of what is experienced today is the result of successful post-war efforts to build affordable housing for waves of inadequately housed immigrants from France's former colonies. Today it is a deindustrialized port city increasingly dependant on the production and consumption of culture. Marseille, Port to Port is a travelogue of an introduction to the city through character sketches of some of the many ordinary people Kornblum has met and spent time with through his years of visitation"--